Endoscopic exploratory tympanotomy in cases of conductive hearing loss with intact tympanic membrane: our experience - Govindan, Shankar Bettadapura; Chandrashekar, Yogeshwar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Determining the cause of conductive hearing loss with an intact tympanic membrane has been a challenge for the otologists for over decades. The aim of this study is to ascertain the usefulness of endoscopes to study the various middle ear pathologies on performing endoscopic exploratory tympanotomy. Methods: A retrospective analysis of various pathologies encountered in the middle ear in 88 patients who underwent endoscopic exploratory tympanotomy done over a study period of 3.5 years (January 2015 to June 2018). Results: In our study, age of the patients ranged from 14 to 50 years with a mean age of 32 years. Most common finding on exploration was otosclerosis in 59 patients followed by revision stapedotomy in 12 patients. 5 patients had normal middle ear findings with all ossicles intact and mobile while other pathologies encountered were tympanosclerosis (4.6%), biscuit foot plate (2.3%), mucosal bands (3.4%) and middle ear developmental anomalies (3.4%). Conclusions: On exploring the middle ear knowing the various aetiologies helps in better preoperative counseling of the patients for the outcome of surgery. Endoscopic approach for exploratory tympanotomy has the benefit of excellent resolution with higher magnification and wider panoramic view of middle ear anatomy.